Russian Federation : Fiscal Transparency Evaluation Update. (IMF Staff Country Reports; Country Report ;, 2019)
Russia was one of the first countries (and first G20 country) to volunteer to pilot the IMF's new Fiscal Transparency Evaluation (FTE). The evaluation was conducted in October 2013 on the basis of a draft version of the IMF's revised Fiscal Transparency Code released for consultation in July 2013. The evaluation report was finalized following comments from the authorities and internal reviews and published in May 2014. In light of feedback from consultation and experience from the pilot FTEs, the Fiscal Transparency Code ('the Code') was further refined, approved by the IMF Executive Board, and published in June 2014.1 As part of the IMF Article IV surveillance mission in May 2019, Russia's progress in improving fiscal transparency and responding the recommendations over the past five years was evaluated. This report provides a summary of the changes to Russia's fiscal transparency practices since 2014 and makes recommendations for further improvements.